التكيف الأكاديمي لدى الطلبة العاملين - بن عزية, دعاء (University of Eloued جامعة الوادي, 2023)
ملخص الدراسة هدفت الدراسة الحالية الى محاولة التعرف على مستوى التكيف الاكاديمي لدى الطلبة العاملين والتعرف على دلالة الفروق في مستوى التكيف في ضوء متغيرات الجنس والحالة الاجتماعية، وإعتمد في الدراسة الحالية على مقياس التكيف الاكاديمي (Henry Borow) والتأكد من خصائصه السيكو مترية ، حيث طبق على عينة قصدية قدرها 130 طالب وطالبة من كلية العلوم الاجتماعية وكلية العوم الإقتصادية بجامعة الشهيد حمه لخضر بالوادي و بإستخدام المنهج الوصفي وقصد الإجابة على التساؤلات الدراسة، تم إستخدام إختبار "ت" لعينة واحدة للكشف على مستوى التكيف الاكاديمي ودراسة الفروق لدى عينة الدراسة تبعاً لمتغير الجنس والحالة الإجتماعية وتوصلت الدراسة الى النتائج التالية:  أن مستوى التكيف الأكاديمي للطلبة العاملين مرتفع.  توجد فروق ذات دلالة إحصائية بين الطلبة العاملين الذكور والطلبة الإناث.  لا توجد فروق ذات دلالة إحصائية بين الطلبة العاملين المتزوجين والغير المتزوجين. وفي ضوء ما توصلت إليه الدراسة الحالية من نتائج فإن هذا الارتفاع قد يعود الى الدافعية للإنجاز والرغبة في النجاح والتطوير النابع من الطلبة ذاتهم ومن هذا المنطلق وجب بضرورة إجراء مزيدا من الدراسات تتعلق بدرجة التكيف الأكاديمي وعلاقتها ببعض المتغيرات كعمر الطالب ونمط الشخصية. Abstract The present study aimed to attempt to identify the level of academic adaptation among working students and to identify the importance of differences in the level of adaptation in the light of gender and social status variables. In the present study, the academic adaptation scale of( Henry Boro) was adopted and its psychometric characteristics were verified, since it was applied to a purposive sample of 130 male and female students from the University of the Martyr Hama Lakhdar in El-Oued. And using the descriptive approach and with the aim of answering the study questions, the "T" test was used on a single sample. The "T" test was also used to study the differences between the study samples in order to answer the previous questions. The results obtained are as follows: -The level of academic adaptation of working students is high. -There are statistically significant differences between male and female students in academic adjustment. -There are no statistically significant differences between married and unmarried students in academic adjustment. In light of what I found Mechanism of the current study results the increase is due to motivation for success and development of the individuals themselves and from this standpoint recommends the need for furher studies lt is related to the degree of academic adaptation and its relationship to som variables such as the student s age and personality type.
تخصص ارشاد و توجيه